2020
DOI: 10.5194/esd-11-737-2020
|View full text |Cite
|
Sign up to set email alerts
|

Emergent constraints on transient climate response (TCR) and equilibrium climate sensitivity (ECS) from historical warming in CMIP5 and CMIP6 models

Abstract: Abstract. Climate sensitivity to CO2 remains the key uncertainty in projections of future climate change. Transient climate response (TCR) is the metric of temperature sensitivity that is most relevant to warming in the next few decades and contributes the biggest uncertainty to estimates of the carbon budgets consistent with the Paris targets. Equilibrium climate sensitivity (ECS) is vital for understanding longer-term climate change and stabilisation targets. In the IPCC 5th Assessment Report (AR5), the stat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
155
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(167 citation statements)
references
References 44 publications
11
155
1
Order By: Relevance
“…The three worst performing models, MIROC-ES2L, CanESM5, and HadGEM3-GC31-LL, in turn, receive less than 1/20 of the equal weighting (about 0.001). Indeed, several recent studies have found that models which show more future warming per unit of greenhouse gas are less likely based on comparison with past observations (e.g., Jiménez-de-la Cuesta and Nijsse et al, 2020;Tokarska et al, 2020). Consistent with their findings, models with high TCR receive very low performance (and combined) weights (label colors in Fig.…”
Section: Weighting Cmip6 Projections Of Future Warming Based On Obsersupporting
confidence: 64%
See 4 more Smart Citations
“…The three worst performing models, MIROC-ES2L, CanESM5, and HadGEM3-GC31-LL, in turn, receive less than 1/20 of the equal weighting (about 0.001). Indeed, several recent studies have found that models which show more future warming per unit of greenhouse gas are less likely based on comparison with past observations (e.g., Jiménez-de-la Cuesta and Nijsse et al, 2020;Tokarska et al, 2020). Consistent with their findings, models with high TCR receive very low performance (and combined) weights (label colors in Fig.…”
Section: Weighting Cmip6 Projections Of Future Warming Based On Obsersupporting
confidence: 64%
“…A summary of weights and warming values for all models as well as all statistics can be found in Tables S2 and S3. Recent studies that use the historical temperature trend as an observational constraint for future warming (e.g., Nijsse et al, 2020;Tokarska et al, 2020) lead to similar conclusions, with lower constrained warming compared with unconstrained (both in the mean and upper percentiles of the distributions).…”
Section: Applying Weights To Cmip6 Temperature Projectionsmentioning
confidence: 69%
See 3 more Smart Citations